Design of a Knowledge Evaluation Questionnaire for Dental Specialists on Preservation and Extraction Indications of the First Permanent Molars - Farnaz Farrokhi; Hamidreza Pakshir; Maryam Karandish; Mehrdad Askarin (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The first permanent molar (FPM) teeth are the most important elements of mastication and are crucial in the improvement of functionally proper occlusion. However, in childhood, these teeth are most susceptible to caries. The loss of an FPM in a child can cause changes in the dental arches. These changes can occur throughout a person's life. In such cases, the dentists and dental specialists need to decide whether to preserve or extract the FPM. Purpose: This study aimed to evaluate the extent of knowledge of dental specialists in Shiraz (Iran) on clinical guidelines for the preservation and extraction indications of FPMs. Materials and Method: The authors developed a dedicated questionnaire for the purpose of knowledge evaluation. A total of 6 orthodontists and 15 dental specialists, respectively confirmed the validity and reliability of the questionnaire. The 19-item questionnaire covered topics such as demographic data, preservation criteria for FPM teeth, and indications for FPM extraction. The survey was carried out across six dental disciplines in Shiraz (Iran) during July-August 2018. The data were analyzed using the SPSS software (version 22.0) with the dependent sample t test and one-way ANOVA. p Value< 0.05 was considered statistically significant. Results: Out of 89 dental specialists, 64 participants (53% male, 47% female) completed the questionnaire. The mean knowledge score for all participants was 10.09±3.93 (maximum of 19). The level of knowledge had a significant and inverse correlation with age (p< 0.001) and years of experience (p= 0.017). It also had a significant relationship with dental specialization (p< 0.001). Conclusion: The overall level of knowledge of the specialists was insufficient, except for the pedodontists and orthodontists. A re-education training program for dental specialists is strongly recommended.